Computation of swimmer's propulsive force profile from active drag parameters with fluctuating velocity in assisted towing - Mason, B.; Sacilotto, G.; Dingley, A. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this research was to identify a mathematical formula to compute a swimmer`s realistic intra stroke propulsive force profile at the swimmer`s maximum mean swim velocity. The intra stroke active drag profile and intra stroke fluctuating velocity profile of the swimmer at maximum mean swim velocity were able to be computed using the assisted towing method, while still allowing the swimmer`s usual intra stroke velocity fluctuations to occur. The computation had only these two profiles and a measure of passive drag at the swimmer`s maximum mean swim velocity to utilise in the formula. Previously, the whole body propulsive force profile had been more easily computed using a constant velocity tow. However, allowing a fluctuating velocity tow provided a more realistic and accurate measure of the swimmer`s true intra stroke propulsive force profile.